Implementasi Program Jaminan Kesehatan Masyarakat (Jamkesmas) di Kabupaten Bantul - Marita Ahdiyana (Yogyakarta State University, 2013)
This research studies about implementation of Jamkesmas program in Bantul Regency to know how reality of implementation and problems surfaced in its implementation. This qualitative research results is that process of target group establishment has followed the procedure even though in the field it is constrained by not updated data. Bantul Regency has done social security (Jamkesos), childbirth security (Jampersal), life saving and the use of SKM. In mechanism how to get service from PPK, significant constrain is not found because of clear SOP. Mechanism and process of PPK claim verification has been done in accordance with provision even though it is often late. In the aspect of organization implementers’ capability, they are reliable because they have been through training. Coordination between program implementers and 11 hospitals in Bantul is done once in every two months. Meanwhile, infrastructure which supports implementation is adequate even though there is no specific fund. The outcome of the policy, in term of financial holding, is transparent and accountable even though it is still constrained by late claim payment. Improvement of the poor people’s access to health services is also caused by the presence of other programs beside Jamkesmas. Keywords: implementation, Jamkesmas, and health service provider (PPK)